Saluran Pemasaran Karet (Hevea brasiliensis) di Desa Batu Mandi Kecamatan Batu Mandi Kabupaten Balangan - Dedy Hermadi; Ana Zuraida; Arief Hidayatullah (JINGLER : Jurnal Teknik Pengolahan Pertanian, 2023)
Rubber is a commodity that is closely related to human daily needs. The productivity of rubber plantations in Indonesia is on average low and the quality of the rubber produced is also less than satisfactory. Even on the world market, Indonesian rubber is known for its low quality. Balangan Regency is one of the regencies in South of Borneo which produces 7,343 tons of rubber (rubber producers), consisting of 1,250 tons of community agricultural production and 6,093 tons of private agricultural production. It was found that there was a decline in production and marketing which had not yet involved institutional marketing institutions. This research uses a survey method with qualitative and quantitative data. The population in this study were all rubber farmers in Batu Mandi Village, Batu Mandi District, Balangan Regency with a cultivated land area of 1 hectare or more. Channel I farmers distribute commodities to factories through collectors. Channel II, farmers sell at low prices to small collectors by asking for lower prices.